Límites y alcances constitucionales de la prisión preventiva desde la jurisprudencia de la corte interamericana de derechos humanos - Arias, Jennifer K. (2020)
The present investigative work was carried out with the general objective of analyzing the constitutional limits and scope of preventive detention from the jurisprudence of the Inter-American Court of Human Rights, under the specific precepts of: analyzing what constitutes the figure of preventive detention; analyze the criteria with which the figure of preventive detention has been regulated in the Ecuadorian legal system; and, analyze the jurisprudential criteria of the Inter-American Court of Human Rights related to preventive detention. Under these indications, the focus of the research was qualitative analysis, under the descriptive type of research, and documentary design, regarding the method used in this research was the dogmatic-legal and as techniques and instruments of information collection, the documentary analysis. Once the objectives were developed and the methodology applied, it was possible to define the scientific problem around determining the limits and the constitutional scope of the Preventive Prison from the jurisprudence of the Inter-American Court of Human Rights, from this study it is concluded that the Court Inter-American human rights has defined the necessary parameters for the adequate and legitimate application of preventive detention, in accordance with the protection of rights and the prevention of their violation, prioritizing the exceptional nature and last ratio of the measure, there are referring cases of jurisprudence in the matter that have served as a guideline for cases resolved at national and international level that have evidenced common errors regarding the lightness of their disposition.